Implementation of Semi Fowler Position to Reduce Shortness of breath on Congestive Heart Failure (CHF) - Amelia, Lia; Karlina, Nonok; Muadi, Muadi (Jurnal Keperawatan Profesional, 2025)
Patient  with congestive heart failure(CHF) often experience shortness of breath due to fluid buildup in the lungsIn the Emergency Department, shortness of breath is a primary complaint requiring prompt and appropriate treatment. Incorrect body positioning can exacerbate symptoms. The semi-Fowler's position is a simple intervention that can increase lung expansion and decrease heart workload. The purpose of this studyTo determine the effectiveness of the semi-Fowler position in reducing shortness of breath in congestive heart failure (CHF) patients in the Emergency Department. The focus of the study is highly relevant to emergency clinical conditions and contributes to nursing practice in the ER, particularly in the initial management of shortness of breath symptoms due to CHF. The study used a case study design, which is appropriate to describe the direct effects of nursing interventions on individual patients in acute conditions. The duration of the intervention (1x7 hours) and respiratory rate measurements are appropriate steps to evaluate clinical changes. The results showed a decrease in respiratory rate from 30x/minute to 24x/minute after the semi-Fowler position intervention, which indicates an improvement in respiratory conditions, indicating that the breathing pattern was partially resolved, meaning the intervention provided benefits but had not completely resolved the problem of shortness of breath. These results are in line with the physiological theory that the semi-Fowler position can reduce diaphragmatic pressure and increase lung expansion.